Disruption of Photomorphogenesis Leads to Abnormal Chloroplast Development and Leaf Variegation in Camellia sinensis - Gao, Xizhi; Zhang, Chenyu; Lu, Cui; Wang, Minghan; Xie, Nianci; Chen, Jianjiao; Li, Yunfei; Chen, Jiahao; Shen, Chengwen (Frontiers in Plant Science, 2021)
Camellia sinensis cv. ‘Yanlingyinbiancha’ is a leaf-variegated mutant with stable genetic traits. The current study aimed to reveal the differences between its albino and green tissues, and the molecular mechanism underlying the variegation. Anatomic analysis showed the chloroplasts of albino tissues to have no intact lamellar structure. Photosynthetic pigment in albino tissues was significantly lower than that in green tissues, whereas all catechin components were more abundant in the former. Transcriptome analysis revealed most differentially expressed genes involved in the biosynthesis of photosynthetic pigment, photosynthesis, and energy metabolism to be downregulated while most of those participating in flavonoid metabolism were upregulated. Collectively, the following conclusions were drawn: (1) repression of the biosynthesis of photosynthetic pigment causes albinism; (2) destruction of photoreceptors in albino tissues suppresses photomorphogenesis, leading to abnormal chloroplast development; (3) albino tissues receive sucrose from the green tissues and decompose their own storage substances to obtain the energy needed for survival; and (4) UV-B signal and brassinosteroids promote flavonoid biosynthesis.